Association of polymorphic markers of the XRCC1, ERCC5, TP53, CDKN1A1 genes with the survival of patients after platinum-based chemotherapy for triple negative breast cancer - T. M. Zavarykina; P. K. Lomskova; M. A. Kapralova; O. O. Gordeeva; I. P. Ganshina; D. S. Khodyrev; S. V. Khokhlova; I. V. Kolyadina (Опухоли женской репродуктивной системы)
Background. Breast cancer is the most common cancer among women. Triple negative breast cancer (TNBC) is the most aggressive subtype of breast cancer, in which there are no special targets for therapy. Therefore chemotherapy is still leading treatment for TNBC including the regiments with platinum drugs.Aim. To study the association of polymorphic markers of the genes XRCC1 (rs25487), ERCC5 (rs17655), TP53 (rs1042522), CDKN1A1 (rs1801270) with progression-free survival (PFS) and overall survival (OS) of TNBC patients after platinum-based neoadjuvant chemotherapy.Materials and methods. Polymorphic markers of the XRCC1, ERCC5, CDKN1A and TP53 genes were studied in blood samples of 67 patients with stage II–III TNBC by real-time polymerase chain reaction with fluorescent allele-specific probes. The results of determining the markers were compared with PFS and OS using the Kaplan–Meyer method and the log-rank-test.Results. The association was found for the polymorphic marker rs25487 of the XRCC1 gene with PFS (carrying the T/T genotype was associated with a decrease of median PFS: 15.6 months versus 34.3 months, p = 0.013) and OS (carrying the T allele was associated with a decrease of median OS: 24.3 months versus 34.6 months, p = 0.041) without depending on the BRCA status. For the polymorphic marker rs17655 of the ERCC5 gene, significant difference in PFS was obtained in the period from 15.4 to 60.0 months of follow-up (the carrier of the C allele was associated with a decrease of median PFS: 20.0 months versus 35.2 months, p = 0.035). When considering the genotypes of the polymorphic marker of the ERCC5 gene differences were revealed between patients with the C/C genotype (M = 15.9 months) and two other genotypes (M = 33.6 months), p = 0.039. For the polymorphic marker rs1801270 of the CDKN1A gene significant differences in PFS were obtained in the period from 15.4 to 60.0 months of follow-up (for carriers of allele A, a decrease in median PFS was observed: 16.6 months versus 32.0 months, p = 0.046). For the polymorphic marker of the TP53 gene (rs1042522) a tendency to decrease OS for carriers of the C/C genotype was found seems promising for further study.Conclusion. The association of the studied polymorphic markers of the genes XRCC1 (rs25487), ERCC5 (rs17655) and CDKN1A (rs1801270) with PFS was revealed in patients with TNBC. Association with OS was obtained for the polymorphic marker of the XRCC1 gene (rs25487). These data may allow for further validation to individualize the treatment of this category of patients.